The Expression of Hormone Receptors as a Gateway toward Understanding Endocrine Actions in Female Pelvic Floor Muscles - Castelán, Francisco; Cuevas-Romero, Estela; Martínez-Gómez, Margarita (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Objective: To provide an overview of the hormone actions and receptors expressed in the female pelvic floor muscles, relevant for understanding the pelvic floor disorders. Methods: We performed a literature review focused on the expression of hormone receptors mainly in the pelvic floor muscles of women and female rats and rabbits. Results: The impairment of the pelvic floor muscles can lead to the onset of pelvic floor dysfunctions, including stress urinary incontinence in women. Hormone milieu is associated with the structure and function alterations of pelvic floor muscles, a notion supported by the fact that these muscles express different hormone receptors. Nuclear receptors, such as steroid receptors, are up till now the most investigated. The present review accounts for the limited studies conducted to elucidate the expression of hormone receptors in pelvic floor muscles in females. Conclusion: Hormone receptor expression is the cornerstone in some hormone-based therapies, which require further detailed studies on the distribution of receptors in particular pelvic floor muscles, as well as their association with muscle effectors, involved in the alterations relevant for understanding pelvic floor disorders.
Keywords: Androgen receptor